Transformation of Yeast by Agitation with Glass Beads - Costanzo, M. C. (1988)
We have found that agitation of Saccharomyces cerevisiae with glass beads and plasmid DNA using a vortex mixer results in genetic transformation of the yeast cells. This method is less efficient, but considerably more convenient, than other yeast transformation procedures. The fact that the minimal requirements for transformation are simply physical damage and the presence of DNA in an osmotically supportive environment suggests that this process may occur in nature.